Visible-light driven photocatalytic degradation of rhodamine B by Ag/Bi2WO6 heterostructures - Anukorn Phuruangrat (2018)
© 2015 Elsevier B.V. All rights reserved. Ag/Bi2WO6 photocatalysts with different silver loadings were synthesized by hydrothermal process and the reduction of silver by sonochemistry. XRD, TEM and XPS revealed the presence of Ag nanoparticles deposited on orthorhombic Bi2WO6 square nanoplates. The photocatalytic degradation of rhodamine B (RhB) by Ag/Bi2WO6 nanocomposites under visible irradiation showed that the deposited Ag nanoparticles greatly improved the photocatalytic efficiency comparing to pure Bi2WO6 nanocrystallites, with 10 wt% Ag/Bi2WO6 at the highest.